Is mesh essential in laparoscopic hiatal hernia repair? analysis of 30-day outcomes from the ACS-NSQIP database over eight years - Wyland, Clayton; Parievsky, Sonia; Madani, Rami; Richter, David M.; Elian, Alain; Shebrain, Saad (Frontiers in Surgery, 2025)
IntroductionUse of mesh to reinforce laparoscopic hiatal hernia repair (LHHR) has been a popular topic of debate among foregut surgeons in recent years. Augmentation with mesh appears to reduce short-term recurrence rates; however, little is known about other important short-term outcomes. Such information is critical to delineating the optimal treatment approach for hiatal hernia. Therefore, this study evaluated various 30-day outcomes in patients who underwent LHHR, both with and without mesh.MethodsAmerican College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database was used to identify patients who underwent LHHR from 2010–2017. Patients were sorted into one of two cohorts: LHHR with mesh or LHHR without mesh. 30-day postoperative mortality, morbidity, length of hospital stay (LOS), operative time, reoperation, and readmission rates were analyzed using SPSS.ResultsA total of 24,488 patients underwent LHHR—9,710 (37.4%) with mesh and 15,318 (62.6%) without mesh. Both groups had similar demographic characteristics. At 30-days, there were no differences between the groups regarding mortality (0.6% vs. 0.6%, p = .990), serious morbidity (3.8% vs. 3.5%, p = .135), overall morbidity (6.4% vs. 6.2%, p = .468), and return to the operating room (2.6% vs. 2.6%, p = .945). However, patients in the mesh group had an increased readmission rate (6.6% vs. 5.8%, p = .013), median [IQR] operative time (147 [108,197] vs. 130 [91,175] minutes, p < .001), and mean LOS (2.9 vs. 2.7 days, p = .002).ConclusionIn this large retrospective cohort study, LHHR with mesh was associated with increased operative time, LOS, and hospital readmission. However, there were no differences in mortality or overall morbidity. These findings provide much needed context to consider prior to employing mesh in LHHR.